PENGARUH PEMANFAATAN APLIKASI BUILDING INFORMASI MODELLING (BIM) TEKLA STRUCTURE EDUCATIONAL TERHADAP PEMBUATAN SHOP DRAWING DAN BILL OF MATERIAL - Deni Putra Arystianto; Achendri M. Kurniawan (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2021)
Abstract Building Information Modelling (BIM) is a representation of a digital system that is very useful especially in the world of construction. Building Information Modelling (BIM) is useful to combine a variety of three-dimensional digital Modelling from various different software and disciplines so as to create a conformity among them. By using Building Information Modelling (BIM) software, efforts to minimize construction failures, fabrication, and others can be achieved, so that in addition to efficient time, we can also streamline quality and also costs.Tekla Structures is a software Modelling, detailing, engineering, drawing, reporting and management with the concept of three-dimensional Building Information Modelling where all structural objects are represented complete with all the information. Modelling with thousands of Profile types, shapes and connections can be done easily, quickly, and reduce errors.In this research will be discussed methods in making Shop Drawing and Bill of Materials a study of buildings with the main structure of Steel, using Tekla Structures software where the output that will be produced is in the form of Shop Drawing such as General Arrangement, Assembly Drawing, Cast Unit Drawing, as well as Single Part Drawing complete with Reports Bill of Materials (BOM) which contains a list of materials and volumes. These output results are certainly very useful and have a significant influence on the needs of a project in the field from planning to construction implementation because of the ease of operation, accuracy of drawing results, and calculations obtained, as well as other detailed information.. Keywords: Building Information Modelling, Tekla Structures, Shop Drawing, Bill of Material